2020
DOI: 10.1002/hep.31298
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Patient‐Derived Xenograft Tumor From Hepatitis C–Associated Liver Cancer and Evaluation of Imatinib Treatment Efficacy

Abstract: Background and Aims Chronic hepatitis C virus (HCV) infection is one of the major causal factors for hepatocellular carcinoma (HCC). The treatment options for HCC are limited for lack of a convenient animal model for study in HCV infection and liver pathogenesis. This study aimed to develop a patient‐derived xenograft (PDX) tumor in mice by using a tumor from a patient with HCV‐associated HCC and evaluating this model’s therapeutic potential. Approach and Results After resection of the primary tumor from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In a sterile environment, NOG mice were anesthetized and the HCC tissue blocks were implanted subcutaneously into the top right flank of the mice. About two months later, after reaching 1 cm in diameter, the subcutaneous PDX tumor nodes were removed, dissected into approximately 2 × 2 × 2 mm 3 pieces, and re-transplanted into the flanks of nude mice for 30 days to permit growth as previously described [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a sterile environment, NOG mice were anesthetized and the HCC tissue blocks were implanted subcutaneously into the top right flank of the mice. About two months later, after reaching 1 cm in diameter, the subcutaneous PDX tumor nodes were removed, dissected into approximately 2 × 2 × 2 mm 3 pieces, and re-transplanted into the flanks of nude mice for 30 days to permit growth as previously described [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…PreS1 protein of HBV stimulates the appearance and self-renewal of LCSCs by activating the expression of c-kit and is confirmed in human hepatoma cells and HCC tissues ( Liu et al, 2017 ). And in HCV infection patients, c-kit overexpression is observed ( Kwon et al, 2015 ; Nazzal et al, 2020 ). Data shows that HCV core protein upregulates the expression of c-kit in hepatocytes, inducing the epithelial-mesenchymal transition, and extends the life span of cells ( Kwon et al, 2015 ).…”
Section: C-kit and Liver Diseasesmentioning
confidence: 99%
“…The roles of c-kit + cells in chronic hepatitis B and C have been described in HCC ( Kara et al, 2008 ; Kwon et al, 2015 ; Liu et al, 2017 ; Nazzal et al, 2020 ). Also, it is reported that there is an increase of mast cells in alcoholic hepatitis, but reports on the relationship between c-kit and alcoholic hepatitis are insufficient ( Farrell et al, 1995 ).…”
Section: C-kit and Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Imatinib (Gleevec, Glivec) is a synthetic tyrosine kinase inhibitor of the breakpoint cluster region-Abelson murine leukemia (Bcr-Abl) fusion gene and is used in the treatment of chronic myeloid leukemia (CML) [ 12 ]. Imatinib has also been used to treat gastrointestinal stromal tumors and various other malignancies [ 13 - 15 ]. GNF-5 is a selective, non-ATP-competitive inhibitor of Bcr-Abl and is used in combination with an ATP-competitive inhibitor, such as imatinib or nilotinib, to enhance antitumor effects in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%